Supramolecular complex sacubitril/valsartan - the first representative of a new class of drugs for the treatment of chronic heart failure - T. V. Ashcheulova; K. M. Kompaniiets; N. M. Herasimchuk (Patologìâ)
The average prevalence of сhronic heart failure in the adult population, according to the statistics of different countries, ranges from 1.5 % to 5.5 % and therefore the study of this problem and of finding new approaches to the treatment of сhronic heart failure is also still relevant at present.